The Role of Job Satisfaction in Mediating the Effect of Transformational Leadership on Employee Performance - Nesia Nasution, Rita; Desy Surya, Elfitra; Muharram Ritonga, Husni (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the role of job satisfaction in mediating the influence of transformational leadership on employee performance at the Human Resources Bureau of the North Sumatra Regional Police. The study employed a quantitative approach with a population of 115 employees. The sampling technique used was saturation sampling, meaning the entire population was included as the study sample. Research data were collected through the distribution of a questionnaire using a Likert scale and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of the SmartPLS 3.0 software. The results indicate that transformational leadership has a positive and significant effect on job satisfaction, with a path coefficient of 0.417, a t-statistic of 7.450, and a p-value of 0.000. Transformational leadership has a positive but insignificant effect on employee performance, with a path coefficient of 0.095, a t-statistic of 1.633, and a p-value of 0.103. Job satisfaction has a positive and significant effect on employee performance, with a path coefficient of 0.649, a t-statistic of 11.708, and a p-value of 0.000. Furthermore, transformational leadership has a positive and significant effect on employee performance through job satisfaction, with an indirect effect coefficient of 0.271, a t-statistic of 5.796, and a p-value of 0.000. These findings indicate that job satisfaction acts as a full mediator in the relationship between transformational leadership and employee performance. Thus, efforts to improve employee performance through the implementation of transformational leadership must be accompanied by efforts to enhance employee job satisfaction.